If you plug in a value of x = 0, then you will get the y-intercept. Similarly if you plug in a value of y = 0, you get the x-intercept.
Plug in x = 0
2(0) + 3y = 12
3y = 12
y = 4
So the y-intercept is 4
Now plug in y = 0
2x + 3(0) = 12
2x = 12
x = 6
So the x-intercept is 6
It's really not all that difficult once your realize it's just plugging in zero for x and y to get the other intercept.
(One thing to note is if you ever have an equation like y = 3, there is no way to plug in x. This tells you there is *no* x-intercept, and the y-intercept is simply 3. Similarly, if you had x = 2, then there is *no* y-intercept and the x-intercept is 2.)
2007-01-02 11:40:07
·
answer #1
·
answered by Puzzling 7
·
3⤊
0⤋
Make it such that it in large condition y = mx + c equation the place the m is gradient and the c is y - intercept: 2x + 3y = 12 3y = 12 - 2x 3y = -2x + 12 y = (-2x + 12)/3 >>>> -2/3x + 12/3 y= -2/3x + 4 So y - intercept is 4
2016-12-15 14:12:00
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Finding the x- and y-intercepts isn't really all that difficult. Just remember this: the x-intercept is what x is equal to when y = 0 and vice versa.
To find the x-intercept, set y equal to zero.
2x + 3(0) = 12
2x = 12
x =6
6 is your x-intercept.
To find the y-intercept, do the same thing you did to find the x-intercept--make the other term equal to zero.
Set x equal to zero.
2(0) + 3y = 12
3y = 12
y = 4
4 is your y-intercept. I hope this helps you understand the concept a little bit better.
2007-01-02 11:50:03
·
answer #3
·
answered by AskerOfQuestions 3
·
1⤊
0⤋
To get the y intercept:
2 x + 3 y = 12
Set x = 0
2(0) + 3 y = 12
3 y = 12
y = 4
To get the x intercept
Set y = 0
2 x + 3 (0) = 12
2x = 12
x = 6
So, the y intercept is at (0,4) and the x intercept is at (6,0)
2007-01-02 11:43:03
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
set x = 0 and solve for y. This will give you the y intercept.
Then, set y=0 and solve for the x intercept.
2*0+3 y = 12
y = 4
2x+3 * 0 = 12
x = 6
2007-01-02 11:42:36
·
answer #5
·
answered by Football_ 1
·
1⤊
0⤋
The x intercept happens when y is zero. That is, the function "intercepts" the x axis.
So, set y to zero and solve:
2x = 12, x = 6
The y intercept happens when x is zero:
3y = 12, so y = 4
2007-01-02 11:39:00
·
answer #6
·
answered by firefly 6
·
1⤊
0⤋
1. Find the y-intercept >
First: replace "0" with the "x" variable:
2(0) + 3y = 12
0 + 3y = 12
3y = 12
Sec: solve for "y" by keeping it on one side > divide both sides by 3:
3y/3 = 12/3
y = 4
2. Find the x-intercept:
First: replace "0" with the "y" variable:
2x + 3(0) = 12
2x + 0 = 12
2x = 12
Sec: solve for "x" by keeping it on one side > divide both sides by 2:
2x/2 = 12/2
x = 6
y - int = 4
x - int = 6
2007-01-02 11:50:11
·
answer #7
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2x + 3y = 12
Divide both sides by 12
x/6 + y/4 = 1 (generalized form x/a + y/b = 1)
X-intercept = 6
Y-intercept = 4
2007-01-02 11:44:32
·
answer #8
·
answered by Sheen 4
·
1⤊
0⤋
2x + 3y= 12 to find the y-intercept, set x=0
3y=12 divide by 3
y=4
to find the x-intercept, set y=0
2x=12 divide by 2
x=6
y-intercept=4
x-intercept=6
2007-01-02 11:38:57
·
answer #9
·
answered by yupchagee 7
·
1⤊
0⤋
2x + 3y = 12
so x = -3/2y + 6 and y = -2/3x + 4
so 6 is the x-intercept and 4 is the y-intercept
2007-01-02 11:39:39
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋